Peran Pendidikan Agama Islam dalam Pelestarian Nilai Budaya Jawa melalui Kesenian Tradisional Ketoprak - Umi Rossy Mardhiyah (Program Studi Pendidikan Agama Islam STAI Senori Tuban, 2026)
The preservation of local culture amid the currents of globalization presents a significant challenge, particularly in shaping the character of the younger generation based on religious values. Traditional ketoprak performance, as part of Javanese culture, holds strategic potential as an educational medium, including for instilling the values of Islamic Religious Education. This study aims to analyze the implementation of Islamic Religious Education in fostering adolescents’ moral development through the preservation of Javanese culture via ketoprak, using Jean Piaget’s learning theory as the analytical framework. This research employs a qualitative method with a descriptive approach, utilizing observation, interviews, and documentation techniques involving adolescents participating in ketoprak activities. The findings reveal that adolescents’ engagement in ketoprak effectively instills Islamic values such as honesty, responsibility, and mutual respect. The internalization of these values occurs not through external coercion but through self-awareness developed from active learning experiences and habitual cultural practices. In conclusion, ketoprak serves not only as a medium for preserving Javanese culture but also as an educational tool in shaping adolescents’ moral character (akhlakul karimah)